Development model Wi-Fi netvork for intrusion prevention - Антипов, Иван Евгеньевич; Василенко, Татьяна Александровна; Михеев, Иван Викторович (Eastern-European Journal of Enterprise Technologies, 2014)
The model structure, which emulates the operation of a wireless Wi-Fi network and takes into account a possibility of intrusions, disruptions and interferences using the Delphi software application, designed solely for testing the offered algorithms of its protection, based on a fuzzy logic, is proposed in the paper. The functions of existing modeling systems, their advantages and disadvantages were analyzed. It was concluded that formerly created software programs are not suitable for this task, so the problem of developing a special model, which emulates the Wi-Fi network operation, designed solely for testing the offered algorithms of its protection, is topical today. The main modeling stages are further considered in the paper. At the first stage, the wireless network operation, implemented by means of a centralized coordination function, is considered. The operation algorithms for separate data transmit/receive sections are given. The procedures, specified by the algorithm, are virtually carried out on different devices. For implementing all algorithms on a computer, they were divided into several non-simultaneous procedures. At the second stage of modeling, the implementation of intruders’ actions is studied. Security threats of wireless networks are considered in detail. Common attacks along with the software implementation such improper activities in the model are described.